O livro didático e as influências ideológicas das imagens: por uma educação que contemple a diversidade social e cultural - Souza, Suely dos Santos (2014)
This study presents an interdisciplinary dialogue between the Education and Design areas, in which, this latter is understood as language and knowledge, here means an image. The aim is to support educators in understanding and addressing the imagistic content of textbooks, especially, the History books which are used in the 5th grade of the Elementary School, because they present the principles of social and cultural construction of our nation and were indicated by the PNLD through the Textbook Guide, 2010-2012 triennium, to be adopted in the Brazilian public education. It is believed the pedagogical importance of image and its contribution to work the imaginary, memory and identification of social and cultural elements, and its capacity to transmit contents, codes, signs and meanings, converted into discourses that dissimulate power relations, stereotypes and prejudices, in a relation of not alterity and disrespect to the differences. In this aspect, the objective of the study is to identify and analyze ideological conceptions that denote racism, stereotypes, prejudice, and discrimination against the black people, in the images of the History books of the 5th year of elementary school, used in public education. Three textbooks, História Projeto Pitanguá, História Projeto Buriti and História, Bahia, were selected, and in these materials, four images of authors, like Debret, Spix and Martius, Rugendas and Guillobel, were chosen in the units concerning to the Colonization and the Regency period, because they are repeatedly the same used in History textbooks, when they refer to the socio-cultural issues of the black people. For the analysis of these images was adopted the qualitative methodology, associated with the iconographic method of Image Analysis, by Erwin Panofsky, and the Discourse Analysis method, from the line that was founded by Michael Pêcheux, which enables the reflection about the composition of these images and the multiplicity of meanings they unveil. This study contributes to the debate about the importance of the interdisciplinary dialogue in the understanding of the printed visual representations in the textbook, which can externalize discriminatory conceptions that need to be elucidated and deconstructed. It was concluded that, despite the many struggles and considerations undertaken by the black social movements and the Academy, these books still have been reproducing and disseminating ethnocentric ideological conceptions that need to be eradicated in the seek for the construction of a truly equal and just society.